Culturing of “Unculturable” Subsurface Microbes: Natural Organic Carbon Source Fuels the Growth of Diverse and Distinct Bacteria From Groundwater - Wu, Xiaoqin; Spencer, Sarah; Gushgari-Doyle, Sara; Yee, Mon Oo; Voriskova, Jana; Li, Yifan; Alm, Eric J.; Chakraborty, Romy (Frontiers in Microbiology, 2020)
Recovery and cultivation of diverse environmentally-relevant microorganisms from the terrestrial subsurface remains a challenge despite recent advances in modern molecular technology. Here, we applied complex natural organic carbon (C), i.e., sediment-derived natural organic matter and bacterial cell lysate, to enrich groundwater microbial communities for 30 days. As comparisons, we also included enrichments amended with simple organic C sources including glucose, acetate, benzoate, oleic acid, cellulose, and mixed vitamins. Our results demonstrate that complex C are far more effective in enriching diverse and distinct microorganisms from groundwater than simple C. Simple C enrichments yield significantly lower biodiversity, and are dominated by few phyla (e.g. Proteobacteria and Bacteroidetes), while microcosms enriched with complex C demonstrate significantly higher biodiversity including phyla that are poorly represented in published culture collections (e.g., Verrucomicrobia, Planctomycetes, and Armatimonadetes). Subsequent isolation from complex C enrichments yielded 228 bacterial isolates representing 5 phyla, 17 orders, and 56 distinct species including candidate novel, rarely cultivated, and undescribed organisms. Results from this study will substantially advance cultivation and isolation strategies for recovering diverse and novel subsurface microorganisms. Obtaining axenic representatives of ‘once-unculturable’ microorganisms will enhance our understanding of microbial physiology and function in different biogeochemical niches of terrestrial subsurface ecosystems.